A LA CARTE PRICING AS A PART OF PRICE MIX OF LOW COST AIR CARRIERS (Perner's Contacts, 2017)
The paper deals with the price mix used by the low cost air carriers with special focus on pricing specifics in case of a la carte pricing. The first part describes price mix specifics by low cost air carriers and the importance of a la carte pricing within this mix. General way-outs are considered when realizing of the analysis focused on specifying of the application degree and form when using a la carte pricing. Gained findings are discussed and evaluated in the conclusion of the paper.
Keywords: a la carte pricing; price mix; air transport; low-cost air carrier